A Conceptual Approach to Identify Factors Affecting the Digital Transformation of Micro, Small and Medium-sized Enterprises (MSMEs) during Covid-19 Pandemic in Indonesia - Ruly - Wiliandri (Ekonomi Bisnis, 2020)
This article aims to identify both internal and external factors that influence the Digital Transformation (DT) process of Micro, Small, and Medium-sized Enterprises (MSMEs) during the  COVID-19 pandemic. The Covid-19 pandemic, which hits all countries including Indonesia, forces business entities, including MSMEs, to digitally transform their business process. The government’s policies on physical distancing and Large-Scale Social Restriction in several regions greatly impacts MSMEs’ activities i.e. decreasing demands or sales up to 60%. The government’s support for improving the telecommunications infrastructure and a digital ecosystem plays an essential role in accelerating DT. Besides, the government’s initiative to establish business centers can also promote DT of the MSMEs. Moreover, this article describes the challenges faced by MSMEs in carrying out DT during the pandemic. This article applied a conceptual approach to explore the influential factors, both internal and external factors of DT process for MSMEs. Besides, this article will explain DT of MSMEs based on capability and the ecosystem perspectives. As this article suggests, considering those factors will broaden our understanding of MSMEs’ efforts to digitalise their business. The digital transformation model via business centers establishment can encourage MSMEs to go digital.